2019
DOI: 10.1111/jar.12578
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among individuals with mild intellectual disability or borderline intellectual functioning in residential care: Examining the relationship between drinking motives and substance use

Abstract: BackgroundThis study examined the relationship between substance use motives (i.e., social, conformity, coping and enhancement) and substance use in individuals with mild intellectual disability or borderline intellectual functioning (MID‐BIF).MethodData were collected among 163 clients with MID‐BIF using interactive questionnaires with visual cues on a tablet with a web application.ResultsResults show that social motives were positively related to frequency of alcohol use, while conformity, coping and enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Regarding coping and enhancementmotivated drinking, our results both corresponded to, and diverged from, those reported in previous studies. Similar to our study, across various populations, drinking alcohol to cope has been found to be associated with diverse measures of problematic drinking, including the DPI scale (Ertl et al, 2018;Gilson et al, 2013;Gilson et al, 2017;Grant et al, 2007;Kuntsche et al, 2005;Nehlin & Öster, 2019;Öster et al, 2017;Schijven et al, 2019), some type of psychological affliction (Beseler et al, 2008;Carpenter & Hasin, 1998;Ertl et al, 2018;Lau-Barraco et al, 2016;Miller et al, 2014;Simons et al, 2005), or painful medical condition . We found two discrepancies between our results and those reported in Gilson et al (2017), where items such as drinking to gain self-confidence and to cope with physical pain increased the odds of being a problem drinker.…”
Section: Problem Drinkers and At High Risk Problem Drinkerssupporting
confidence: 83%
See 2 more Smart Citations
“…Regarding coping and enhancementmotivated drinking, our results both corresponded to, and diverged from, those reported in previous studies. Similar to our study, across various populations, drinking alcohol to cope has been found to be associated with diverse measures of problematic drinking, including the DPI scale (Ertl et al, 2018;Gilson et al, 2013;Gilson et al, 2017;Grant et al, 2007;Kuntsche et al, 2005;Nehlin & Öster, 2019;Öster et al, 2017;Schijven et al, 2019), some type of psychological affliction (Beseler et al, 2008;Carpenter & Hasin, 1998;Ertl et al, 2018;Lau-Barraco et al, 2016;Miller et al, 2014;Simons et al, 2005), or painful medical condition . We found two discrepancies between our results and those reported in Gilson et al (2017), where items such as drinking to gain self-confidence and to cope with physical pain increased the odds of being a problem drinker.…”
Section: Problem Drinkers and At High Risk Problem Drinkerssupporting
confidence: 83%
“…A plausible explanation is that non-problem drinkers were alcohol consumers in the process of developing drinking problems (at high risk problem drinkers), former problem drinkers, or former problem drinkers at risk of relapse. The research evidence based on longitudinal studies on drinking trajectories in the context of poor mental health point in this direction ( Brennan, Schutte, Moos, & Moos, 2011 ; Schutte et al, 2009 ; Schutte et al, 2001 ; Schutte et al, 2006 ). That is, drinking in order to cope appears to have a potent function in the development, continuation, and relapse of drinking problems, especially when a person with a tendency to experience strong affect lacks alternatives to alcohol to cope with stressors, or uses avoidance or escape coping strategies in the acceptance of, or the escape from, negative thoughts and emotions (Schutte et al, 2009 ; Schutte et al, 2001 ; Schutte et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El estudio de Didden et al (2009) señala que la población con discapacidad intelectual puede tener menos habilidades para relajarse y, por ello, pueden consumir alcohol o cualquier otra sustancia con el fin de reducir la ansiedad (i. e., reforzamiento negativo) o para aumentar los pensamientos y sensaciones placenteras que llevan a un estado de relajación (i. e., reforzamiento positivo). El alivio del malestar psicológico fue también señalado por los tres estudios restantes (Kerr et al, 2016;Schijven et al, 2019;Taggart et al, 2007b).…”
Section: Factores Predictores Y Variables Que Influyen En El Consumo De Alcohol En Personas Con Discapacidad Intelectualunclassified
“…Children with low average cognitive ability represent a substantial proportion of children with often unrecognised difficulties 1,2 . Early deficits in cognitive ability are associated with later adverse outcomes in many domains of life including mental and physical health, educational attainment, socio‐economic status and substance use 3–7 . Despite the well‐established adverse impacts, approximately 13% of children whose cognitive ability falls into this lower range receive little attention in scientific literature and often little recognition in ordinary life 2 …”
Section: Introductionmentioning
confidence: 99%